Practitioners suggestions to overcome the Shari'ah audit challenges in Malaysian Islamic financial institutions - Muhammad Shahid, Muhammad Shahid; Bhatti, Farhad Ahmed; Hassan, Rusni; Khaliq, Ahmad; , (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2022)
The constant advancement of Islamic financial institutions requires highly qualified experts in Islamic finance administrations, to ensure that all transactions made by Muslims and non-Muslims conform to the Shari’ah conditions. Certainly, an appropriate method of audit is required for the IFIs to persist in growing and providing assurance that they are rigorously ensuring the Shari’ah in all features (of their products, rules, and processes, and contracts). The current study intends to seek suggestions from Shari’ah audit practitioners to meet the current gap in the Shari’ah audit practice further to ensure Shari’ah audit transparency in IFIs in Malaysia. The study employed a quantitative method involving 40 practitioners in the Shari’ah assessment services through a purposive sampling procedure from several Islamic banks and Takaful operators in Klang Valley, Malaysia. Data were gathered employing a structured questionnaire and analysed using descriptive statistical instruments, including frequency, percentage, averages, and standard differences due to the descriptive nature of this study. The results suggest that awareness of the Shari’ah audit among them is satisfactory, as most of them learnt Shari’ah audit through additional training. The findings also demonstrate that there is an absence of an independent audit report, an independent audit framework for the Shari’ah audit, and incompetent Shari’ah auditors in this practice. The study reveals that the Shari’ah audit service has a significant potential to become a marketable job shortly. In due course, to cultivate grander awareness, this study also suggests integrating Shari’ah audit-related courses into higher-learning institutions and incorporating them into the professional courses for students and professionals in order to produce competent and capable Shari’ah auditors. The study contains a few limitations such as the sample area for the study being confined to Klang Valley area. This research is also unable to perform ANOVA on religious differences as the sample consisted of largely Muslim respondents. Due to these factors, the generalisation of the study’s findings will be visibly restricted. This study is a comprehensive proposal for IFIs, whereby it suggests effective and curative solutions for the existing challenges to overcome Shari’ah audit challenges.